Meu projeto de vida hoje é morrer aos 90 anos ou mais : etnografia realizada em um núcleo para a terceira idade na UFPB - Detmering, Edilza Maria Medeiros (2024)
This study aims at investigating and understanding the aging process of people who attend courses from the Núcleo Integrado de Estudos e Pesquisa da Terceira Idade (NIETI – Integrated Center for Studies and Research on the Third Age) in the Federal University of Paraíba, within the scope of their daily lives and life projects. It is also interesting to investigate and identify the ‘views about the elderly’ or the ‘perspectives regarding aging’ in the institution’s mission, and the perspective that these people have of the space in which they study. From 2020 onwards, the objective of this study underwent an expansion, as there was a newfound interest in unveiling the strategies to which the subjects have developed in order to face the challenges imposed by social isolation (the main preventive strategy against Covid-19 at the time), as well as investigating the impacts of the pandemic in their daily lives and in the construction of their life projects. The categories of greatest interest in this study are: ‘life projects’, ‘third age’, ‘old age(s)’, ‘generation’, ‘youth’. The field of the research was developed between 2019 and 2023, and it was used in-person and virtual tools. As methodological contribution, the following modalities were implemented: observant participation, participant observation, informal conversations, interviews, technological resources (WhatsApp, Telegram, Google Meet), theatrical presentations and the group’s own production (informational pamphlets and the class blog). In terms of theoretical framework, a broad spectrum was used, encompassing anthropological, scenic and pedagogical literature. Among the most determining collaborations are Debert (1994, 1999), Camarano (2002, 2016), Goldenberg (2013, 2016, 2020), Lins de Barros (1997, 2006, 2018), Britto da Motta (2010), Longhi (2018, 2019) and Gilberto Velho (1994), regarding the anthropological reflections; Boal (1980, 2002) and Grotowski (1971) in terms of theatrical production; Chianca (2010) and Cardim & Santos (2014) in the pedagogical context. After the necessary analyses, it was found that these people have approached the term ageless. They dream, plan and project their lives forward, towards the future.